2018
DOI: 10.1007/s10902-018-9976-0
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Relationship Between Physical Activity and Happiness

Abstract: This study aimed to examine the relationship between physical activity and happiness through systematically reviewing the existing literature. A systematic search of major databases including PubMed/Medline, PsychInfo, SportDiscus, and Embase was performed in 2017 for original research articles published post-1980 with the related keywords of happiness and physical activity. From 1142 retrieved records, fifteen observational studies (thirteen cross-sectional studies and two longitudinal studies) and eight inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
134
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 51 publications
(112 reference statements)
13
134
1
3
Order By: Relevance
“…Although a large body of literature already showed that LTSA is associated with higher well-being and life satisfaction (Wiese et al 2018;White et al 2017;Zhang and Chen 2019), this paper contributes to the state of knowledge by pointing out several relevant specifications of this relationship. First, we showed that the amount of LTSA is associated with life satisfaction as well as with satisfaction in the domains of leisure, appearance, social relations, work and health.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Although a large body of literature already showed that LTSA is associated with higher well-being and life satisfaction (Wiese et al 2018;White et al 2017;Zhang and Chen 2019), this paper contributes to the state of knowledge by pointing out several relevant specifications of this relationship. First, we showed that the amount of LTSA is associated with life satisfaction as well as with satisfaction in the domains of leisure, appearance, social relations, work and health.…”
Section: Resultsmentioning
confidence: 88%
“…Positive links between physical activity and well-being were found in all age groups, including youths (McMahon et al 2017), students (Jetzke and Mutz 2019), adults (Downward and Dawson 2016;Marques et al 2016) and the elderly (Lera-López et al 2017). Recent reviews based on observational and intervention studies (Wiese et al 2018;White et al 2017;Zhang and Chen 2019) conclude that even small amounts of additional physical activity lead to significant increases in wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study [13] analyzed the long-term effects of LTPA on happiness and indicated that people who continue participating in LTPA for 2 and 4 years could reduce the likelihood of unhappiness compare to those who were physically inactive. Recently, Zhang and Chen [14] systematically reviewed 23 studies on the association between physical activity and happiness, found that as little as 10 minutes of physical activity per week or one time of doing physical activity per…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is generally presumed to be associated with experiences of happiness in adolescents [7,8]. An extensive set of studies has shown that there is a positive association between physical activity and happiness in the wider population, including adolescents (for a review see: [9]). More speci cally, previous cross-sectional studies have demonstrated a positive association between self-reported physical activity and mental well-being [10,11] or happiness in adolescents [12][13][14].…”
mentioning
confidence: 99%
“…Second, the aforementioned studies were not designed to test the directionality of the association between physical activity and happiness as they used cross-sectional designs or lacked repeated measures of either physical activity or happiness [9,27,28]. To determine the directionality, longitudinal (or repeated) observations are needed [29].…”
mentioning
confidence: 99%